Nematicidal effect of Beauveria species and the mycotoxin beauvericin against pinewood nematode Bursaphelenchus xylophilus - Sánchez-Gómez, Tamara; Harte, Steven J.; Zamora, Paula; Bareyre, Matéo; Díez, Julio Javier; Herrero, Baudilio; Niño-Sánchez, Jonathan; Martín-García, Jorge (Frontiers in Forests and Global Change, 2023)
Introduction and main objective Bursaphelenchus xylophilus, commonly known as pine wood nematode (PWN), is considered one of the greatest threats to European and Asian pines. Regarding its management, most efforts have been directed toward control measures for the major vector (Monochamus spp.) and screening for genetic resistance in its hosts. However, an integrated pest management strategy which also implements pinewood nematode control is currently lacking. The aim of this study was to evaluate the nematicidal effect of two Beauveria species, a genus well known for its entomopathogenic activity. Summary methodology For this purpose, in vitro antagonism tests of fungi (Beauveria bassiana and B. pseudobassiana) and the mycotoxin beauvericin (C45H57N3O9) on B. xylophilus populations were conducted. Finally, the production of beauvericin in B. bassiana and B. pseudobassiana strains was quantified by high-performance liquid chromatography - mass spectrometry (HPLC-MS). Results and discussion Both the B. bassiana and B. pseudobassiana fungal species and the mycotoxin beauvericin showed a clear nematicidal effect on B. xylophilus populations, substantially reducing their survival rate and even attaining 100% mortality in one case. HPLC-MS analysis confirmed and quantified the production of beauvericin by B. bassiana and demonstrated for the first-time beauvericin production in B. pseudobassiana. Final conclusion These findings highlight the potential of Beauveria species and the mycotoxin beauvericin to be implemented in an integrated pest management strategy to control both nematode and vector.